Time series and spatial distribution of tuberculosis in Oyo state Nigeria - Teibo, Titilade Kehinde Ayandeyi (2023)
The virulence of Tuberculosis (TB) in the population makes it imperative to intensify studies on the disease caused by Mycobacterium tuberculosis. TB most frequently affects the lungs (pulmonary TB) and may also affect other organs (extra-pulmonary TB). There are few studies on TB using spatial and temporal approaches, especially in African countries. Therefore, the aim of the present study was to describe the epidemiological profile of TB and analyze the spatial distribution and temporal trend of TB incidence and mortality in Oyo state Nigeria from 2015-2019. The study comprises TB cases reported by the Oyo State Ministry of health between 2015 and 2019. The spatial analysis technique was applied to analyze the spatial distribution of incidence and mortality rate of TB. To identify areas with spatial dependence of TB, the Gi* technique was used through the ArcGis 10.5 software. The time series analysis technique was applied to assess the behavior of TB in Oyo state over the period studied. A total of 28,680 cases of pulmonary and extrapulmonary TB and 1,131 TB deaths were reported in all local governments of Oyo state between 2015 and 2019. The highest cases rate occurred in Ibadan South west local government (334 cases per 100,000), with the single local government area (LGA) having more than 10% cases of all 33 LGAs. Ido and OluyoleLGAs were hotspot regions for TB with a 99% confidence interval. The historical series of theTB incidence rate slightly increased between 2015 to 2017, with a sharp declinefrom then until 2019, but the temporal trend for the incidence of TB in the period under study decreased. While a slight increase in the TB mortality rate throughout the analyzed period wasobserved, the temporal trend of the event between 2015 and 2019 showed an increase. Advancing knowledge by highlighting areas of risk for the occurrence of TB (hotspots) and its relationship with social and economic inequality remains fundamental to theachieving the goals of public health actions. The results of the present study contributed to the knowledge of the epidemiological profile, spatial and temporal distribution, and areas with a higher risk of tuberculosis transmission in Oyo state and Nigeria as a whole. This information allows policymakers to target hotspot areas for intervention and disease prevention.